Appraisal of Passive and Active Fire Protection Systems in Student’s Accommodation - Ismail, I.; Taib, M.; Othuman Mydin, M.A. (EDP Sciences, 2014)
Fire protection systems are very important systems that must be included in buildings. They have a great significance in reducing or preventing the occurrences of fire. This paper presents an assessment of fire protection systems in student’s accommodation. Student accommodation is a particular type of building that provides shelter for students at University. In addition, it is also supposed to be an attractive environment, conducive to learning, and importantly, safe for occupation. The fire safety of occupants in a building, must be in accordance with the requirements of the building’s code. Therefore, the design of the building must comply with the Uniform Building By- Law (UBBL) 1984 of Malaysia, and provide all of the required safety features. This paper describes the findings from investigations of passive and active fire protection systems installed in buildings, based on fire safety requirements, UBBL (1984).